2017
DOI: 10.1016/j.vaccine.2017.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative functional potency of DNA vaccines encoding Plasmodium falciparum transmission blocking target antigens Pfs48/45 and Pfs25 administered alone or in combination by in vivo electroporation in rhesus macaques

Abstract: Antibodies recognizing conformational epitopes in Pfs48/45, an antigen expressed on the surface of Plasmodium falciparum gametes and zygotes, have firmly established Pfs48/45 as a promising transmission blocking vaccine (TBV) candidate. However, it has been difficult to reproducibly express Pfs48/45 in a variety of recombinant expression systems. The goal of our studies was to evaluate functional immunogenicity of Pfs48/45 using DNA vaccine format in rhesus macaques. An additional goal was to ensure that when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…We have shown improved functional immunogenicity of the Pfs25 DNA vaccine through codon-optimization and in vivo electroporation (EP) [ 26 , 27 ] and by a heterologous DNA prime-protein boost regimen in higher mammals [ 25 ]. Pfs25 DNA vaccine has also been evaluated by immunization in mice and nonhuman primates when combined with another TBV DNA vaccine, Pfs48/45, and specific antibody responses to both antigens and transmission-blocking activity were not compromised [ 28 , 29 ]. These studies provide compelling rationale for combining Pfs25 with other vaccine candidates targeting different lifecycle stages for developing more effective vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown improved functional immunogenicity of the Pfs25 DNA vaccine through codon-optimization and in vivo electroporation (EP) [ 26 , 27 ] and by a heterologous DNA prime-protein boost regimen in higher mammals [ 25 ]. Pfs25 DNA vaccine has also been evaluated by immunization in mice and nonhuman primates when combined with another TBV DNA vaccine, Pfs48/45, and specific antibody responses to both antigens and transmission-blocking activity were not compromised [ 28 , 29 ]. These studies provide compelling rationale for combining Pfs25 with other vaccine candidates targeting different lifecycle stages for developing more effective vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…8.1 | Use of pilot grant programs to provide an opportunity for discovery and collaboration Indeed, numerous successes in animal model development (Burwitz, et al, 2017a(Burwitz, et al, , 2017bLopez et al, 2014), vaccine testing (Coban et al, 2004;Datta et al, 2017;Petersen et al, 2014), and drug treatment efficacy have arisen from NHP pilot studies. Examples of pilot studies that successfully utilized limited numbers of macaques include a study of five macaques that demonstrated the persistence of the Lyme disease pathogen following a recommended treatment protocol (Embers et al, 2012a) and subsequently devised a strategy for diagnostic test development (Embers et al, 2012b), and a study of four macaques that demonstrated expression of the human NTCP receptor on hepatocytes is sufficient to support full HBV infection of macaques (Burwitz et al, 2017a).…”
Section: Capitalizing Upon Established Efforts and Resourcesmentioning
confidence: 99%
“…One approach is to increase the efficiency of plasmid-based DNA vaccination by electroporation (EP). In vivo EP is an efficient vaccine strategy that enhances cell permeability, local tissue inflammation, and immunogenicity in experimental animals [ 22 , 23 , 24 , 25 , 26 , 27 ] and in humans [ 28 , 29 , 30 , 31 ]. When EP is applied to the target organism, the encoded antigens are expressed and elicit the corresponding immune response, with the potential to induce antibody-mediated, helper T cell-mediated, and cytotoxic T cell-mediated immune responses [ 32 ].…”
Section: Introductionmentioning
confidence: 99%